Exploring the ring-closing metathesis for the construction of the solomonamide macrocyclic core: identification of bioactive precursors - Cheng-Sánchez, Iván; Sánchez-Ruiz, Antonio; Martínez-Póveda, Beatriz Amparo; Medina-Torres, Miguel Ángel; Carrillo Fernández, Paloma; Rodríguez-Quesada, Ana María; López-Romero, Juan Manuel; Sarabia-García, Francisco Ramón (My University, 2018)
New synthetic strategies directed toward the novel cyclopeptides solomonamides have been explored utilizing an olefin metathesis as the key reaction. In the various strategies investigated, we worked on minimally oxidized systems, and the olefin metathesis reaction demonstrated efficiency and validity for the construction of the macrocyclic core. The described synthetic strategies toward the solomonamides are well suited for the subsequent access to the natural products and represent flexible and diversityoriented routes that allow for the generation of a variety of analogues via oxidative transformations. In addition, preliminary biological evaluations of the generated solomonamide precursors revealed antitumor activity against various tumor cell lines.
Keywords: Cáncer; Metathesis; Solomonamide; Bioactive precursors; Antitumor